The The Effect of Peer Support Group Method Stunting Prevention Education on Mothers' Knowledge and Children's Nutritional Status in Benculuk Village, Cluring District, Banyuwangi - Irfa Lailatul Ni'mah Irfa; Siti Maimunah; Atik Badi’ah (Professional Health Journal)
Introduction: Stunting is still a problem that often occurs in toddlers,Lack of understanding about nutrition and stunting in mothers can increase the risk of stunting. One of the steps that can be taken to reduce cases of stunting is to spread knowledge about stunting evenly to mothers.